Intracellular pHluorin as Sensor for Easy Assessment of Bacteriocin-Induced Membrane-Damage in Listeria monocytogenes - Crauwels, Peter; Schäfer, Leonie; Weixler, Dominik; Bar, Nadav S.; Diep, Dzung B.; Riedel, Christian U.; Seibold, Gerd M. (Frontiers in Microbiology, 2018)
Listeria monocytogenes is a food-borne pathogen that frequently causes disease outbreaks around the world with fatal outcomes in at-risk individuals. Due to its extreme tolerance to a wide range of stress conditions, L. monocytogenes is challenging to control in food production and processing environments and throughout food storage. Bacteriocins are antimicrobial peptides naturally produced by many bacteria and were shown to be effective against various pathogens including L. monocytogenes. Thus, bacteriocins are a promising solution to prevent contaminations with L. monocytogenes and microorganisms during food production and preservation. Additionally, bacteriocins have the potential to reduce or completely replace antibiotics in animal feed, where they are widely used as growth enhancers thereby massively contributing to the global problems of antibiotic resistance. However, current approaches to identify, purify and characterize bacteriocins are limited to time- and labor-intensive genome mining and growth-dependent assays. In the present study, we constructed a derivative of L. monocytogenes EGD-e expressing the pH-sensitive fluorescent protein pHluorin as a sensor strain to detect disruption of the pH gradient by the membrane-damaging activity of bacteriocins. The ratiometric fluorescence properties of pHluorin were validated both in crude extracts and permeabilized cells. The sensor strain was used to assess membrane damaging activity of the bacteriocins nisin A and pediocin PA-1 and to determine the minimal concentrations required for full disruption of the pH gradient across the membrane. Moreover, the sensor strain proved useful to analyze the presence of compounds affecting membrane integrity in supernatants of a nisin Z-producing Lactococcus lactis strain at different timepoints during growth. Supernatants of this strain that were active in disrupting the pH gradient across the membrane were also shown to inhibit growth of L. monocytogenes. In summary, the presented results suggest that the generated sensor strain is a convenient, fast and reliable tool to identify and characterize novel bacteriocins and other compounds that target membrane integrity.